A computer-based testing system to evaluate protective relays as a tool in power system protection education - Martins, L. Sousa (2013)
Teaching power system relaying is a fundamental issue in a power system high-level course. However, for an effective instruction of this topic an experience with real equipments can be considered as fundamental. To achieve this purpose, in this paper a new approach for the practical learning of power system relaying is presented. This consists of a computer-based testing system of relay-operating characteristic. Different relay types and developed specific software are also an important piece of the laboratory practice. Using this system it is possible to understand the performance and limitations of different protective relay systems and to test a real relay disoperation. The benefit of using this system is not available through traditional lectures and textbooks.